Self-reported Measures of Strength and Sport-Specific Skills Distinguish Ranking in an International Online Fitness Competition. Issue 12 (December 2018) - Serafini, Paul R.; Feito, Yuri; Mangine, Gerald T.
Abstract : Abstract: Serafini, PR, Feito, Y, and Mangine, GT. Self-reported measures of strength and sport-specific skills distinguish ranking in an international online fitness competition. J Strength Cond Res 32(12): 3483–3493, 2018—To determine if self-reported performance measures could distinguish ranking during the 2016 CrossFit Open, data from 3, 000 male ( n = 1, 500; 27.2 ± 8.4 years; 85.2 ± 7.9 kg; 177.0 ± 6.5 cm) and women ( n = 1500, 28.7 ± 4.9 years; 63.7 ± 5.8 kg; 163.7 ± 6.6 cm) competitors was used for this study. Competitors were split by gender and grouped into quintiles (Q1–Q5) based upon their final ranking. Quintiles were compared for one-repetition maximum (1RM) squat, deadlift, clean and jerk (CJ), snatch, 400 m sprint, 5, 000 m run, and benchmark workouts (Fran, Helen, Grace, Filthy-50, and Fight-Gone-Bad). Separate one-way analyses of variance revealed that all competitors in Q1 reported greater ( p ⩽ 0.05) 1RM loads for squat (men: 201.6 ± 19.1 kg; women: 126.1 ± 13.0 kg), deadlift (men: 232.4 ± 20.5 kg; women: 148.3 ± 14.5 kg), CJ (men: 148.9 ± 12.1 kg; women: 95.7 ± 8.4 kg), and snatch (men: 119.4 ± 10.9 kg; women 76.5 ± 7.6 kg) compared with other quintiles. In addition, men in Q1 (59.3 ± 5.9 seconds) reported faster ( p ⩽ 0.05) 400 m times than Q3 only (62.6 ± 7.3 seconds), but were not different from any group in the 5, 000 m run. Women in Q2 (67.5 ± 8.8 seconds) reported faster ( p ⩽ 0.05) 400 m times than Q3–Q5 (73.5–74.8 seconds), and faster (21.3 ± 1.8 minutes, p < 0.02) 5, 000 m times than Q4 (22.6 ± 2.2 minutes) and Q5 (22.6 ± 1.9 minutes). Faster ( p ⩽ 0.05) Fran times were reported by Q1 (men: 138.2 ± 13.3 seconds; women: 159.4 ± 28.3 seconds) compared with other groups, while the results of other workouts were variable. These data indicate that the most successful athletes excel in all areas of fitness/skill, while lower-ranking athletes should focus on developing strength and power after achieving sufficient proficiency in sport-specific skills.